A comparison of cardinal gaze speed between Major League Baseball players, amateur prospects, and non-athletes - Kubitz, K.; Roberts, C.-M.; Hunfalvay, M.; Murray, N. (Journal of Sports and Performance Vision, 2020)
Purpose: Sensorimotor variables have been shown to predict performance in professional baseball players. However, cardinal gaze speed in baseball players has received only limited attention. This study tested the hypothesis that the cardinal gaze speed in Major League Baseball (MLB) players would be faster than in amateur prospects and non-athletes.